2014
DOI: 10.1371/journal.pone.0088712
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aptamers against Exon v10 of CD44 Inhibit Breast Cancer Cell Migration

Abstract: CD44 adhesion molecules are expressed in many breast cancer cells and have been demonstrated to play a key role in regulating malignant phenotypes such as growth, migration, and invasion. CD44 is an integral transmembrane protein encoded by a single 20-exon gene. The diversity of the biological functions of CD44 is the result of the various splicing variants of these exons. Previous studies suggest that exon v10 of CD44 plays a key role in promoting cancer invasion and metastasis, however, the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Furthermore, isoform-specific antibodies have been reported, including those against CD44v6, where a radiolabeled CD44v6 monoclonal antibody showed selective tumor targeting and high tumor uptake in a nude mouse squamous cell carcinoma xenograft [ 87 ]. In addition to antibody-based targeting of CD44, other strategies have been employed using DNA aptamers targeting CD44v10 in breast cancer [ 88 ] and peptides mimicking CD44v6 for blocking the coreceptor function of CD44v6 for c-Met and VEGFR-2 in endothelial cells thereby impeding angiogenesis [ 89 ]. In an effort to develop new and effective treatment strategies for advanced-stage ovarian cancer patients, CD44 is also being explored as a therapeutic target.…”
Section: Therapeutic Targeting Of Cd44mentioning
confidence: 99%
“…Furthermore, isoform-specific antibodies have been reported, including those against CD44v6, where a radiolabeled CD44v6 monoclonal antibody showed selective tumor targeting and high tumor uptake in a nude mouse squamous cell carcinoma xenograft [ 87 ]. In addition to antibody-based targeting of CD44, other strategies have been employed using DNA aptamers targeting CD44v10 in breast cancer [ 88 ] and peptides mimicking CD44v6 for blocking the coreceptor function of CD44v6 for c-Met and VEGFR-2 in endothelial cells thereby impeding angiogenesis [ 89 ]. In an effort to develop new and effective treatment strategies for advanced-stage ovarian cancer patients, CD44 is also being explored as a therapeutic target.…”
Section: Therapeutic Targeting Of Cd44mentioning
confidence: 99%
“…DNA aptamers were isolated based on their binding to exon v10 of CD44 by SELEX technology (Iida et al 2014). In breast cancer cells, CD44v10 proteins appear to form complexes with the surface protein EphA2, which accounts for the migratory ability of the cells (Iida et al 2014). This complex formation is impaired by the treatment of the breast cancer cells with the v10-specific aptamers, and consequently, the migration of the breast cancer cells is inhibited.…”
Section: Other Strategies Against Cd44mentioning
confidence: 99%
“…A previous study reported that CD44v6 is an important indicator in PTC cell differentiation, and the expression of CD44v6 is significantly higher in malignant lesions compared with non-malignant lesions ( 7 ). CD44 + /CD24 − cells are more aggressive than CD44 − cells, not only in PTC, but also breast and ovarian cancer ( 8 10 ). However, the underlying mechanism that promotes CD44 + cells to exhibit a more malignant phenotype remains unknown.…”
Section: Introductionmentioning
confidence: 99%